Pengaruh Komitmen Organisasi Dan Iklim Organisasi Terhadap Kinerja Karyawan - Rudi Azhar; Yulpa Rabeta; Yuli Eprianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research was conducted to determine the effect of organizational commitment and organizational climate on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Lubuklinggau. and analyze the most influential variables on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Lubuklinggau. The population in this study were all employees at PT. Bank Negara Indonesia (Persero) Tbk Lubuklinggau, as many as 54 people and using the formula from Issac Michael as the sample was 47.22 rounded up to 47 respondents. The problem of this research is that the services provided to customers are not yet optimal, and the employee's performance is not yet optimal in terms of developing public service programs that are in accordance with the needs of the community .By using descriptive quantitative method. Based on the data analysis, it can be concluded: Organizational Commitment (X1) and Organizational Climate (X2) partially have a positive and significant effect on employee performance, meaning that it supports Ha. It is known that the results of the study can be seen that the Fcount value is 31,090 with a significant level of 0.000 while Ftable with =5% and (nk-1) or (47-2-1) = 44. And the numerator (k-2) is 3,209 . Fcount (31.090) > Ftable (3.209), meaning that Ho is rejected and Ha is accepted. This shows that there is a significant effect between Organizational Commitment and Organizational Climate on Employee Performance. With the commitment between employees and a harmonious organizational climate, it will maximize the performance achieved by employees so far.